143k views
1 vote
Help me answer this question please

Help me answer this question please-example-1
User Danizmax
by
4.8k points

1 Answer

4 votes

For this case we must find the inverse of the following function:


f (x) = x ^ 2 + 7

For this we follow the steps below:

Replace f(x) with y:


y = x ^ 2 + 7

We exchange the variables:


x = y ^ 2 + 7

We solve the equation for "y", that is, we clear "y":


y^ 2 + 7 = x

We subtract 7 on both sides of the equation:


y ^ 2 = x-7

We apply square root on both sides of the equation to eliminate the exponent:


y = \pm\sqrt {x-7}

We change y by
f ^ {- 1} (x):


f ^ {- 1} (x) =\pm\sqrt {x-7}

Answer;

Option A

User Xiao Liang
by
6.0k points